HYPERCONTENT DEVELOPMENT TRAINING FOR RICH AND RENEWABLE LEARNING RESOURCES AT STATE SENIOR HIGH SCHOOL 1 DRIYOREJO, GRESIK - Gunawan, Wawan; Atiqoh, Atiqoh; Fatirul, Achmad Noor; Rahmawati, Retno Danu; Sabariah, Sabariah; Rufii, Rufii; Sitompul, Nurmida Catherine; Kurniawan, Andri (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
This community service activity aims to provide Hypercontent Development Training for Rich and Renewable Learning Resources. at SMA Negeri 1 Driyorejo, Gresik as a good researcher for teachers. Specifically, this activity aims to Bind Interaction in Learning at SMA Negeri 1 Driyorejo, Gresik smoothly and in accordance with the even semester period of the 2023-2024 academic year. The methods used in this PPM activity include lectures or counseling containing the delivery of information for general and theoretical materials, in this case the material (1) Application of Hypercontent Development Training for Rich and Renewable Learning Resources, (2) Excavation Hypercontent Development Training for Rich and Renewable Learning Resources. The PPM activities that have been implemented have run smoothly in accordance with the expected goals of this program, and have obtained good results. The lecturers who presented received knowledge sharing on how to practice Hypercontent Development Training for Rich and Renewable Learning Resources at SMA Negeri 1 Driyorejo, Gresik. The high school teachers received additional knowledge about Hypercontent Development Training for Learning Resources. The Hypercontent Development Training Program for Learning Resources in addition to receiving positive responses from teachers of SMA Negeri 1 Driyorejo, Gresik, also received responses from supervisors in the Driyorejo District Education Office Branch, Gresik Regency. The training participants hope that the Hypercontent Development Training for Learning Resources can be continued in the future considering the benefits of this program. Furthermore, the institutional cooperation that has been well established between UNIPA Postgraduate School, especially the Department of Educational Technology with the Driyorejo District Education Office Branch, Gresik Regency is expected to continue in the future as part of the Tri Dharma of Higher Education.